2012
DOI: 10.1186/1746-4358-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding knowledge, attitude and practice among school teachers in Abha female educational district, southwestern Saudi Arabia

Abstract: BackgroundInadequate knowledge, or inappropriate practice, of breastfeeding may lead to undesirable consequences. The aim of this study was to assess breastfeeding knowledge, attitude and practice (KAP) among female teachers in the Abha Female Educational District and identify factors that may affect breastfeeding practice in the study population.MethodsA cross-sectional study using a self-administered questionnaire was conducted among school teachers in Abha Female Educational District during the months of Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
94
17
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(130 citation statements)
references
References 18 publications
17
94
17
2
Order By: Relevance
“…Our EBF findings were similar to a study in Addis Ababa, Ethiopia which found 29.3 % prevalence of EBF under six months [9], while it was higher than a study in Abha female educational district, Saudi Arabia in which EBF for 6 months was reported only by 8.3 % of participants (n = 32) [6] and a study in Kinshasa, Congo that found only 2.8 % of infants were exclusively breastfed (n =12) [7].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our EBF findings were similar to a study in Addis Ababa, Ethiopia which found 29.3 % prevalence of EBF under six months [9], while it was higher than a study in Abha female educational district, Saudi Arabia in which EBF for 6 months was reported only by 8.3 % of participants (n = 32) [6] and a study in Kinshasa, Congo that found only 2.8 % of infants were exclusively breastfed (n =12) [7].…”
Section: Discussionsupporting
confidence: 73%
“…In Saudi Arabia only by 8.3 % (n = 32) of the 384 participants EBF for 6 months [6]. In a study in Congo, 87.5 % of infants were EBF during the maternity stay, but by six months, only 2.8 % (n = 12) of infants were exclusively breastfed [7].…”
Section: Introductionmentioning
confidence: 99%
“…But, this finding was higher than that of the national prevalence, 52% {32}. The prevalence of exclusive breast feeding in this study higher than that of reported in previous study in Brazil, 4%, Bangladesh, 16%, Saudi Arabia, 8.3 %, Rwanda, 38%, Congo, 2.8%, Malaysia, 43.1%, Nigeria ,16.4%, Meerut, 34.8% [13][14][15][16][17]33,35]. In Ethiopia reported low prevalence in Mizan Aman town, 26.4 %, Addis Ababa ,29.3 %, North Gondar, 35.9%, Southern Ethiopia, 48.2%, Arba Minch Zuria, 55.6% , Gedeo , 57.6 %, Debre Markos, 60.8%, District of Debre Markos town and Gozamen, 55% and 64% respectively [19][20][21][22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 54%
“…Study showed that the prevalence of EBF in Brazil 4% , Bangladesh 16%, Rwanda 38%, Saudi Arabia 8.3 %, Congo 2.8 %, of infants were exclusively breastfed [14][15][16][17]. In Ethiopia the range of prevalence of EBF less than six months were 24.4 % -81.1% [19][20][21][22][23][24][25][26][27][28][29].…”
mentioning
confidence: 99%
“…It is contrary with the scientific fact that colostrum contains antibodies that is crucial to baby's health 2 . This customary belief was accustomed in other ethnicities, all over the world 1,19 . Mothers in this study also linked breastfeeding to the psychological development few studies in Malaysian found similar results 21. It could be observed that mothers would associate breastfeeding and motherhood as beautiful experience that woman can have the entire life.…”
Section: Discussionmentioning
confidence: 99%